Factors Affecting the Performance Risk of Banks Listed on the Indonesia Stock Exchange - Radhiyya, Khalisha; Sopandi, Destya Amelia Rachmawati; Leon, Farah Margaretha (ProBisnis : Jurnal Manajemen, 2024)
This study aims to identify variables that affect the performance of banks listed on the Indonesia Stock Exchange. The addition of cost efficiency variables as independent variables is a novelty of this study. This research method involves collecting data from 17 banking companies over a six-year period (2017–2022), and applying data processing analysis using panel data regression analysis techniques. The results of the study found that Capital has a positive impact on Liquidity (LIQ) and Cost Efficiency has a positive impact on Return on Assets (ROA). The implication for financial managers is to choose the best way to utilize assets to achieve business goals, especially to improve shareholder welfare. This study emphasizes the importance of capital and cost efficiency for investors when choosing investment opportunities in banking companies in Indonesia.